Strength training in children and adolescents: Morphological and neuronal adjustments? - Paoli, A.; Moro, T. (EWF Scientific Magazine, 2016)
It has been widely demonstrated how RT is capable of increasing strength in children by means of increased muscle activation (+ 13- 17% MU activation) and a 16.8% increase in EMG after respectively 10 weeks and 8 weeks. Such changes can be attributed to improved muscle recruitment and an improved synchronisation of motor units with mechanisms which are substantially different from those of adults. Therefore, children respond better to high repetitions and light loads. We can therefore conclude that it is important to stimulate with a load that mainly aims at increasing muscle recruitment and the synchronisation of motor units, as recent studies have shown. In addition to strengthening exercises with small gym equipment, exercises and progressive training for the classic Olympic lifts are equally important. When properly performed, these exercises and the preparatory training are in fact, capable of accentuating the nervous action, rather than only pure muscular action (even if loads are to be used and not overlooked), thus acting on factors that can be better trained in this age bracket. In conclusion, therefore, the improvement of strength with RT in the development phase comes about by correct nerve stimulation, using suitable loads which allow maximum recruitment; whereas it has been proven of little use, at least until the onset of puberty, to work on techniques that tend to stimulate hypertrophy. Maximum force is to be sought as it provides an important stimulation for muscular synchronisation. However, techniques designed to increase muscle mass are prohibited. Children recover much faster than adults and this should be kept in mind in the recovery stages of both maximal strength exercises and endurance training.